Analisis Prioritas Perbaikan Infrastruktur Dasar Desa Pematang Tujuh Kecamatan Rasau Jaya Kabupaten Kubu Raya - Heri Azwansyah (Jurnal Serambi Engineering, 2024)
Adequate village infrastructure can facilitate all social and economic activities of the community. The overall objective of this study was to identify the priorities and strategies for infrastructure improvement in the village of Pematang Tujuh. Data were collected through observation and interviews. Data analysis includes priority analysis and strategies for infrastructure improvement. This study found that the priority for infrastructure improvement is the agricultural sector with an accessibility score of 11.32. The priority for improving access in the agricultural sector is to repair/improve farm roads and market access roads. Road improvements will be carried out by improving the quality of roads through concrete or asphalt paving, and by widening village roads so that they can be used by four-wheeled vehicles. Transport facilities are needed in the market sector with an accessibility score of 10.68. Improving the accessibility of transport facilities takes the form of organising public transport or village transport as a means of village transport. Treatment in terms of priority facilities is carried out in the clean water sector with a facility accessibility value of 16.57. Strategies to improve accessibility in the clean water sector can be done by adding rainwater reservoirs (PAH) or installing clean water networks